" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Y=a(x-xp)²+yp
-3=a(0-(-1)²+(-4)
-3=a(0+1)²-4
-3=a(1)²-4
-3=a-4
-3+4=a
1=a
Y=a(x-xp)²+yp
Y=1(x-(-1)²+(-4)
Y=(x+1)²-4
Y=x²+2x+1-4
Y=x²+2x-3
(x+3)(x-1)
x=-3 dan x=1
f(x)≤0 interval -3≤x≤1 maka L(D)=-ₐ∫ᵇ f(x) dx
L(D)=- ₋₃∫¹(x²+2x-3)dx
=-₋₃∫¹(1/3x³+x²-3x)
=- ((1/3(1)³+(1)²-3(1))-((1/3)(-3)³+(-3)²-3(-3))
=- ((1/3(1)+1-3))-((1/3)(-27)+(9)+9)
=- ((1/3)-2)-((-9)+18)
=- ((1/3-6/3)-(9)
=- ((-5/3)-(27/3)
=- (-32/3)
=- (-10 2/3 )
= 10 2/3 satuan luas
Pilihan E.
Demikian Semoga Membantu dan Bermanfaat!